Uptake of Non-Transferrin Iron by Erythroid Cells. (14th November 2010) - Prus, Eugenia; Fibach, Eitan
Abstract : Most of the iron in the plasma is bound to transferrin (Tf) and is taken up by cells through their surface Tf receptors (TfRs). Under pathological conditions of iron-overload, the plasma iron which is in excess of the binding capacity of Tf is present as non-Tf-bound iron. We probed the uptake of non-Tf iron and its consequences on the oxidative status of peripheral RBC and reticulocytes as well as developing erythroid precursors grown in vitro. The cells were exposed to ferrous ammonium sulfate under Tf-supplemented and Tf-free conditions. Using flow cytometry techniques, we found that both the TfR-deficient mature RBC and their TfR-containing precursors at all stages of maturation can take up non-Tf iron that accumulates as redox-active labile iron and generates reactive oxygen species. Such a mechanism may account for ineffective erythropoiesis of developing precursors in the bone marrow and for the shortening of the lifespan of mature RBCs in the circulation.